Ancient pottery of the late bronze period in western Siberia and Kazakhstan - Y., Dubyagina (Opción, 2019)
The article discusses the characteristics of ancient ceramics of the Late Bronze period in the territory of Western Siberia and Kazakhstan. The research methodology includes both traditional for archeology methods of studying sources, and methods borrowed from the arsenal of natural and exact sciences. As a result, the comparative characteristics of Western Siberia and Kazakhstan in the late Bronze period clearly show cultural and historical differences in the formation of these communities. In conclusion, fragments of ceramics with the inclusion of small pieces of ore and slag were found.